PERAN KRITIS ETIKA DAN PROFESIONALISME DALAM MEMBENTUK KINERJA SAKSI AHLI JASA KONSTRUKSI - Silaen, Marojahan Koster; Pangaribuan, Wanapri; Hutajulu, Olnes Yosefa (Jurnal Insinyur Profesional, 2025)
This in-depth study explores the critical role of ethics and professionalism in shaping the performance of a construction expert witness. In the complex context of the construction environment, where expert testimony significantly impacts dispute resolution, a profound understanding of ethics and professionalism becomes crucial. The research investigates how ethical aspects, such as integrity, transparency, and honesty, synergize with the level of professionalism of expert witnesses to create optimal performance. Through a qualitative research approach, data was collected through in-depth interviews with experienced construction expert witnesses, which were then analyzed to identify relevant patterns and findings. The research findings provide profound insights into how the integrity and professional demeanor of an expert witness influence the validity and reliability of their testimony. The results offer practical guidance for construction professionals, lawyers, and other stakeholders to understand the importance of maintaining high ethical standards and professionalism in the context of construction expert testimony. Thus, this research contributes to the literature on professional ethics in construction law and lays the groundwork for the development of practical guidelines for expert witnesses.